Contrasting future lightning stories across Europe. (1st November 2022) - Kahraman, Abdullah; Kendon, Elizabeth J; Fowler, Hayley J; Wilkinson, Jonathan M
Abstract: Thunderstorms are the most common source of hazardous weather at local scales, but are poorly represented in conventional climate models, resulting in high uncertainty in future changes. How these changes manifest in terms of lightning is even more uncertain, with previous studies giving conflicting projections. Here, for the first time, we use a km-scale model that explicitly resolves convection across Europe; suggesting more convection by 2100 under RCP8.5. Our ice-based lightning scheme indicates a highly altered lightning climatology-the consequence of general increases in instability, partly limited by convective inhibition, along with huge increases in melting level height and less cloud ice. A northward shift in favourable weather regimes increases lightning frequency at higher latitudes, and favours more thunderstorms over the Alps, but lightning decreases over lower terrain elsewhere and over the sea. Our results suggest the need to re-evaluate lightning risk to wildfires, properties, and human life across Europe.